DNA Methylation and Hydroxymethylation in Cervical Cancer: Diagnosis, Prognosis and Treatment - Zhu, Hongming; Zhu, He; Tian, Miao; Wang, Dongying; He, Jiaxing; Xu, Tianmin (Frontiers in Genetics, 2020)
Recent discoveries have led to the development of novel ideas and techniques that have helped elucidate the correlation between epigenetics and tumor biology. Nowadays, the field of tumor genetics has evolved to include a new type of regulation by epigenetics. An increasing number of studies have demonstrated the importance of DNA methylation and hydroxymethylation in specific genes in the progression of cervical cancer. Determining the methylation and hydroxymethylation profiles of these genes will help in the early prevention and diagnosis, monitoring recurrence, prognosis, and treatment of patients with cervical cancer. In this review, we focus on the significance of aberrant DNA methylation and hydroxymethylation in cervical cancer and the use of these epigenetic signatures in clinical settings.